Methodology for Organizing Project-Based Activities in Fine Arts Lessons - Xasanova Sitora Shuhrat qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
ANNOTATION: This article analyzes the methodological foundations, content, and significance of organizing project-based activities in fine arts lessons. The project-based approach is considered an effective tool for developing students’ independent thinking, creative imagination, aesthetic taste, and practical artistic skills. Based on the scientific views of S.A. Shovdirov and other modern pedagogical researchers, the paper explores the didactic possibilities of the project method, its stages of implementation in the classroom, and its pedagogical effectiveness. The study concludes that the use of project-based learning in art education increases student engagement, deepens their understanding of artistic processes, and provides conditions for realizing their creative ideas in practice.